The Effect of Different Sources of Selenium Supplementation on the Meat Quality Traits of Young Charolaise Bulls during the Finishing Phase - Silvia Grossi (Antioxidants, 2021)
The aim of the study was to compare the effects of sodium selenite (SS), selenium yeast (SY), and hydroxy-selenomethionine (OH-SeMet) on the meat quality and selenium (Se) deposition of finishing beef cattle. Sixty-three bulls were distributed over 3 treatments and fed SS, SY, or OH-SeMet at 0.2 mg kg−1 dry matter (DM) for 60 d. None of the Se sources affected the growth performance or carcass characteristics. OH-SeMet showed a higher Se transfer to the meat than SS or SY (p < 0.01). SY and OH-SeMet reduced the shear force of the meat (p < 0.0001), improved pH (p < 0.001), and reduced the drip losses (p < 0.001) and the lipid oxidation of the meat (p < 0.001). During 8 d of storage, OH-SeMet showed higher levels of meat lightness (L*) and yellowness (b*) than SS (p < 0.001), while the SY meat showed a higher L* than SS, albeit only on d 6. OH-SeMet improved b*, compared to SS, and also compared to SY on days 4, 7, and 8 (p < 0.001). Supplementing beef with SY and OH-SeMet improved several meat quality parameters. OH-SeMet appears to be the most effective strategy to improve the Se content and color stability of beef cattle meat.